Good enough - Salvador Barberà; Geoffroy De Clippel; Alejandro Neme; Kareen Rozen (Brown University, Department of Economics, 2018)
A decision maker may not perfectly maximize her preference over the feasible set. She may feel it is good enough to maximize her preference over a sufficiently large consideration set; or just require that her choice is sufficiently well-ranked (e.g., in the top quintile of options); or even endogenously determine a threshold for what is good enough, based on an initial sampling of the options. We introduce and investigate a class of theories, Order-k Rationality, encompassing heuristics such as these.
Keywords: 330